Political Education And Digital Literacy: Strategies To Counter Disinformation In Public Space - Lathifah Sandra Devi; Muhammad Asmawi; Rizqi Nur Khabibah (Universitas Negeri Gorontalo, 2026)
The development of the digital public sphere has intensified the spread of political disinformation, affecting the quality of democracy and the public’s informational resilience. The primary objective of this study is to formulate a political education strategy integrated with digital literacy to address disinformation in the public sphere. This research employs a descriptive qualitative approach with a case study design, utilizing in-depth interviews, participatory observation, and document analysis. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that integrative-curricular, participatory-dialogic, and collaborative-digital strategies are effective in enhancing students’ ability to verify information, think critically, and develop ethical awareness as digital citizens. The integration of political education and digital literacy has proven capable of fostering digital civic immunity that is adaptive to the dynamics of digital democracy and the challenges of disinformation. Therefore, digital literacy-based political education emerges as a relevant pedagogical strategy for strengthening the quality of the democratic public sphere in the digital era.